Genome walking of chitinase gene in Sago Palm - Saiful Shakirin, Bin Rosli (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Metroxylon sagu which is known as "balau" is a type of plant where its trunk has highly content of starch. The discovery of Metroxylon sagu chitinase gene (MsChi) is important in plant defense response against fungal pathogen. It is a type of protein that catalyzes the hydrolysis of the β-1, 4- linkages of N-acetyl-D-glucosamine polymer of chitin which is a major component of the exoskeleton of insects. In order for some gene to be expressed, regulatory element is required in regulating their expression. This project was aimed to determine the regulatory elements for chitinase gene expression via genomic walking. CTAB method which has been modified is applied for the extraction of total genomic DNA of the sago palm. Via primer-based genomic walking method, the upstream region of chitinase gene in sago palm will be isolated and send for sequencing. However, since no band can be obtained after PCR re-amplification, DNA sequencing step cannot be proceed.